Youth and Women's Rights: A Teaching Project in a Public Elementary School (Interdisciplinary Studies Journal, 2024)
This work aims to present the actions of a teaching project, carried out in partnership with the Women's Secretariat of the municipality of Santana do Maranhão/MA, which aims to promote workshops in municipal public schools on the types of violence against women, expanding the scope of knowledge of adolescent girls and young women about abusive relationships and other forms of violence. The city of Santana do Maranhão, located in the Lower Parnaíba region of Maranhão, faces difficulties in accessing a network of services for women victims of violence – including the lack of a Specialized Women's Police Station (DEAM) and a Public Defender's Office – making women who experience this reality in their daily lives more vulnerable, contributing to the underreporting of cases. Thus, given this context, the Women's Secretariat, in partnership with the Federal University of Maranhão, has been carrying out campaigns and actions since August 2022. From this close dialogue between the university and municipal management, the idea to propose a teaching project focused on schools emerged, with the aim of combating this type of violence and spreading knowledge about women's rights through education, as well as training teachers to handle gender and sexuality issues in a sensitive and respectful way, through awareness and education of students, through lectures, films, classroom discussions, and public acts. The workshops aim to create an inclusive educational environment based on gender equality, Human Rights, combating all forms of violence, grounded in an education engaged in the process of building a less unequal society, inserted in a plural and diverse world.
Keywords: Women's Rights; Public Schools; Santana do Maranhão; Violence Against Women